A Child Patient with Eyelid Involvement of Liken Planus - Gulhan Gurel; Sevinç Şahin; Betül Aytekin; Emine Çölgeçen (Galenos Publishing House, 2019)
Liken planus (LP) which was first defined by Erasmus Wilson in 1869, is a pruritic dermatosis with unknown etiology affecting skin and mucosa. It is characterized with purple, scaly, flat polygonal papular lesions placed on flexor surface of wrist and legs and oral and genital mucous membranes. LP is rarely seen in children and constitutes only 1-4% of total cases. Eyelid involvement is rarely reporting finding of LP which is an inflammatory disease. Here, a 9-year-old child with LP is presented with very rare localized involvement such as eyelids.